Implementasi Strategi Pemasaran Untuk Meningkatkan Penjualan di Galeri Ciumbuleuit Hotel - Lilis Putri Anggraeni; Chandra Hendriyani (Akademi Sekretari Manajemen Taruna Bakti, 2021)
The growing of the tourism sector in various parts of the world makes a big competition occur by promoting the superiority of each country that is not owned by other countries. In this issue there will definitely be ups and downs or increases and decreases that have link with the tourism sector. To stay ahead in the fierce market competition, a good and correct marketing strategies is needed for to not lose the competition and still exist in the tourism. This supports the writing of a practical work report entitled